Characterization of Synthetic Tf2 as a NaV1.3 Selective Pharmacological Probe - Mathilde R. Israel; Thomas S. Dash; Stefanie N. Bothe; Samuel D. Robinson; Jennifer R. Deuis; David J. Craik; Angelika Lampert; Irina Vetter; Thomas Durek (Biomedicines, 2020)
NaV1.3 is a subtype of the voltage-gated sodium channel family. It has been implicated in the pathogenesis of neuropathic pain, although the contribution of this channel to neuronal excitability is not well understood. Tf2, a β-scorpion toxin previously identified from the venom of Tityus fasciolatus, has been reported to selectively activate NaV1.3. Here, we describe the activity of synthetic Tf2 and assess its suitability as a pharmacological probe for NaV1.3. As described for the native toxin, synthetic Tf2 (1 µM) caused early channel opening, decreased the peak current, and shifted the voltage dependence of NaV1.3 activation in the hyperpolarizing direction by −11.3 mV, with no activity at NaV1.1, NaV1.2, and NaV1.4-NaV1.8. Additional activity was found at NaV1.9, tested using the hNav1.9_C4 chimera, where Tf2 (1 µM) shifted the voltage dependence of activation by −6.3 mV. In an attempt to convert Tf2 into an NaV1.3 inhibitor, we synthetized the analogue Tf2[S14R], a mutation previously described to remove the excitatory activity of related β-scorpion toxins. Indeed, Tf2[S14R](10 µM) had reduced excitatory activity at NaV1.3, although it still caused a small −5.8 mV shift in the voltage dependence of activation. Intraplantar injection of Tf2 (1 µM) in mice caused spontaneous flinching and swelling, which was not reduced by the NaV1.1/1.3 inhibitor ICA-121431 nor in NaV1.9-/- mice, suggesting off-target activity. In addition, despite a loss of excitatory activity, intraplantar injection of Tf2[S14R](10 µM) still caused swelling, providing strong evidence that Tf2 has additional off-target activity at one or more non-neuronal targets. Therefore, due to activity at NaV1.9 and other yet to be identified target(s), the use of Tf2 as a selective pharmacological probe may be limited.